KARAKTERISTIK PETANI PADI PESERTA PROGRAM UPAYA KHUSUS PADI JAGUNG KADELAI (UPSUS PAJALE) DI DESA RAMBAH BARU KECAMATAN RAMBAH SAMO KABUPATEN ROKAN HULU - Indrawan, Rizky; Yulida, Roza; Kausar, Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research aimed to analyze the internal and external characteristicsof paddy farmers Special Effort Paddy Corn Soy (UPSUS PAJALE) in Rambah Baru village. This research was conducted in Rambah Baru village, Rambah Samo dictricts, Rokan Hulu regency. Determination oflocation by Multi-Stage Sampling based of considerations in Rokan Hulu there was an area thatapplying UPSUS PAJALE program.The Methodscorrespond conducted census.The total sample for this research was 52 farmers. The data analyzes of this researchused descriptive method and Likert Scale.The result showed the internal characteristics of paddy farmers atRambah Baru villageviewedbase of farmers age criteriaare at the productive age 15-55 years old, the majority of farmers education wasSenior high school , number of family burdenmajority about ≤ 4 people, long experience farming 19-35 years old, farmers's land area majorityabout 0.56 to 2 Ha and cosmopolitan of the farmers was high.The external characteristics of paddy farmers were high seen from the intensity extension with a score of 3.90, the accuracy of channel extension included in the high category with a score of 3.54, the amount of resources included in the category of high 3.70, affordability means of production included in the medium category with a score of 3.30, availability of production facilities included in the medium category with a score of 2.92 and the environmental carrying capacity in the high category with a score of 3.61. Recapitulation where the highest intensity of extension in the high category with a score of 3.90 and the lowest was the availability of production facilities included in the medium category with a score of 2.92. Keywords:Characteristics, Paddy Farmers, Special Effort Paddy Corn Soy (UPSUS PAJALE)